Corduroy mansions [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Corduroy Mansions novel, 2010)
Corduroy Mansions is the nickname given to a building in London's vibrant Pimlico neighborhood, home to a captivating collection of quirky characters. The author traces their amusing foibles and interactions through the ins and outs of neighborliness in all its unexpected variations.